The Position of Science From The Islamic Perspective (Analysis of Surat al-Taubah Verse 122) - Abdul Aziz Romdhoni; Sofi Anaba Fauziah (Penerbit Hellow Pustaka, 2023)
The development of human civilization is closely related to the mastery of knowledge possessed by the people. This is because science plays an important role as the basis for the progress of a civilization. This article aims to examine the position of Science in the View of the Islamic Religion on the interpretation of Al-Quran sura al-T'aubah verse 122. This research is a qualitative research using interpretation analysis. From this study it was concluded that between Islam and science both are interrelated and have an important role in life. The importance of the role of science in the life of Muslims is very high , so that the integration of science and religion is an obligation because this will provide opportunities for the development of science which always relies on religious values .